ASSESMENT OF BIOCHEMICAL AND IONIC ATTRIBUTES AGAINST SALT STRESS IN EGGPLANT (Solanum melongena L.) GENOTYPES - Z. Mustafa; C. M. Ayyub; M. Amjad; R. Ahmad (Journal of Animal and Plant Sciences, 2017)
Biotic and abiotic factors contribute in yield loss of horticultural crops, but the salinity is one of foremost concern. Salinity is dilemma in vegetable production in lowering quality and yield. Eggplant is a high value vegetable crop, playing important role in combating malnutrition and increasing income of farming community. Pot culture experiment was conducted to study the ionic and biochemical changes in eggplant genotypes (Saadia-tolerant and Black Beauty-sensitive) under different salinity levels (control, 3, 6, 9, 12 and 15 dS m-1) of NaCl. The enzymatic activities such as superoxide dismutase (SOD), catalase (CAT), peroxidase (POD) and osmolytes [glycine betaine (GB) and proline] were substantially increased in both tested eggplant genotypes under salt stress. Tolerant genotype (Saadia) performed better than sensitive one for these variables. Whereas malondialdehyde contents (MDA) were maximum in sensitive (Black Beauty) with increasing salinity levels. Among the ionic traits, Na+ and Cl- were enhanced while Ca2+ and K+ considerably reduced in response to increasing saline water stress. Whereas, tolerant genotype maintained the high concentration of beneficial ions (Ca2+ and K+) and the minimum amounts of lethal ions (Na+ and Cl-). The study elaborated that tolerant genotype showed positive enzymatic and ionic response against salinity stress levels.
Keywords: Antioxidants; biochemical; eggplant; GB; ionic changes; MDA; proline; salinity